Clinically Relevant Extended-Spectrum β-Lactamase–Producing Escherichia coli Isolates From Food Animals in South Korea - Song, Jihyun; Oh, Sung-Suck; Kim, Junghee; Park, Sukyoung; Shin, Jinwook (Frontiers in Microbiology, 2020)
Extended-spectrum β-lactam antimicrobials have been broadly used in food animals and humans to control infectious diseases. However, the emergence and rapid spread of extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae, mainly Escherichia coli, have seriously threatened global health in recent decades. In this study, we determined the prevalence, antimicrobial susceptibility, and genetic properties of ESBL-producing E. coli (ESBL-EC) strains isolated from food animals in South Korea. A total of 150 fecal samples from healthy chickens (n = 34), pigs (n = 59), and cattle (n = 57) were screened from January to July 2018. Among these, 77 non-duplicate cefotaxime-resistant ESBL-EC strains were isolated from 32 chicken, 41 pig, and 4 cattle samples, with the corresponding occurrence rates of 94.1%, 69.5%, and 7.0%, respectively. All the isolates showed multidrug resistance (MDR) and produced at least one type of β-lactamase, including CTX-M (98.7%) and TEM (40.3%). CTX-M-14 (53.1%), CTX-M-55 (53.7%), and CTX-M-65 (50.0%) were the predominant genotypes in the chicken, pig, and cattle samples, respectively. Multilocus sequence typing revealed 46 different sequence types (STs), including the human-associated extraintestinal pathogenic E. coli ST131 (n = 2), ST10 (n = 5), ST38 (n = 1), ST410 (n = 4), ST354 (n = 2), ST58 (n = 3), ST117 (n = 1), and ST457 (n = 1). To the best of our knowledge, this is the first report of pandemic E. coli ST131 in non-human isolates in South Korea. Our results demonstrate the high prevalence and diversity of MDR-ESBL-EC in food animals and highlight them as potential pathogenic ESBL-EC reservoirs that may pose a high-risk to human health.